Bis(acetylacetonato)copper(II) – structural and electronic data of the neutral, oxidized and reduced forms - Conradie, Jeanet (Data Brief, 2019)
Bis(acetylacetonato)copper(II) can be synthesized economically and with ease by the reaction between acetylacetone and a copper salt (Cu(OAc)(2) or CuCl(2)·2H(2)O). When used as catalyst, bis(acetylacetonato)copper(II) is sometimes being oxidized to Cu(III) or reduced to Cu(I), although only the structure of the neutral form is known experimentally. The content of this paper provides computational chemistry calculated data of the geometry, electronic structure, spin state and frontier orbitals for the neutral, as well as the oxidized and reduced forms of the bis(acetylacetonato)copper(II) molecule. This data shows that both the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of the neutral molecule are copper based. The neutral molecule is a spin = ½ system. The data shows that the spin state of both the oxidized and reduced molecules is zero.